A Hybrid Approach Based on Grey Correlation Analysis and Fuzzy Comprehensive Judgment for Evaluating Service Quality of Passenger Train - Wanxiang Wang; Qi Zhao; Ruijun Guo (Advances in Mechanical Engineering, 2015)
The satisfaction of passengers plays an important role in choosing the transportation mode which directly influences train service quality. Based on passengers’ needs, the evaluation index system of train service quality was built. A field example was applied in Chinese high-speed rail, G33 passenger train. The evaluation value of service quality can be calculated by the hybrid method based on grey correlation analysis (GCA) and fuzzy comprehensive judgment (FCJ). The result indicates that the index system and the integration of GCA and FCJ could effectively evaluate passenger train service quality.